Taper Embedded Phase-Shifted Fiber Bragg Grating Fabricated by Femtosecond Laser Line-by-Line Inscription - Feng Zhu; Zhe Zhang; Changrui Liao; Ying Wang; Lei Xu; Jun He; Chao Wang; Zhengyong Li; Tianhang Yang; Yiping Wang (IEEE Photonics Journal, 2018)
We demonstrate a phase-shifted fiber Bragg grating with a taper induced by femtosecond laser micromachining. In this configuration, a fiber taper fabricated by an arc discharge in a fiber splicer was sandwiched between two fiber Bragg grating sections, which were formed using femtosecond laser line-by-line inscription. The degree of phase shift produced by this device can be adjusted by introducing axial strain, with a sensitivity of 4.59 pm/μϵ. A theoretical study was also conducted by modeling the taper under axial strain. The relative deviation between simulated and measured sensitivities is less than 10%.